2020
DOI: 10.1038/s41598-019-56787-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-step plasma-induced hierarchical structures for tunable water adhesion

Abstract: Smart surfaces in nature have been extensively studied to identify their hierarchical structures in micro-/nanoscale to elucidate their superhydrophobicity with varying water adhesion. However, mimicking hybrid features in multiscale requires complex, multi-step processes. Here, we proposed a one-step process for the fabrication of hierarchical structures composed in micro-/nanoscales for superhydrophobic surfaces with tunable water adhesion. Hierarchical patterns were fabricated using a plasma-based selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The plasma etching during 120 s led to a surface with an unexpected morphology, presenting several nanoholes associated with the exaggerated degradation of the PLA surface due to plasma etching confirmed by FTIR and XPS (Figure ). The prolongation of plasma etching leads to the formation of nanoholes on the surface of the PLA film due to physical and chemical etching reactions by various chemical species present in the cold argon plasma (e.g., electrons, radicals, and ions), leading to the loss of organic matter in the film during etching. , In addition, these reactions end up removing with time the hard etching masks (copper and silver clusters) on the polymer surface, which have a slower etching rate than PLA . The wings of the black butterfly (Pachliopta aristolochiae) have a surface with micro- and nanoholes capable of increasing the absorption of the spectrum of electromagnetic radiation emitted by the sun, and these bioinspired surfaces has been applied to improve the performance of photovoltaic cells …”
Section: Resultsmentioning
confidence: 99%
“…The plasma etching during 120 s led to a surface with an unexpected morphology, presenting several nanoholes associated with the exaggerated degradation of the PLA surface due to plasma etching confirmed by FTIR and XPS (Figure ). The prolongation of plasma etching leads to the formation of nanoholes on the surface of the PLA film due to physical and chemical etching reactions by various chemical species present in the cold argon plasma (e.g., electrons, radicals, and ions), leading to the loss of organic matter in the film during etching. , In addition, these reactions end up removing with time the hard etching masks (copper and silver clusters) on the polymer surface, which have a slower etching rate than PLA . The wings of the black butterfly (Pachliopta aristolochiae) have a surface with micro- and nanoholes capable of increasing the absorption of the spectrum of electromagnetic radiation emitted by the sun, and these bioinspired surfaces has been applied to improve the performance of photovoltaic cells …”
Section: Resultsmentioning
confidence: 99%
“…In addition, plasma etching can produce high aspect ratio features. Ko et al [ 107 ] found that plasma-based selective etching can be used to fabricate SH surfaces with high aspect ratio nanostructures. They proposed a one-step process to fabricate hierarchically structured SH surfaces with tunable water adhesion by plasma-based selective ion etching supported by the dual scale etching mask.…”
Section: Micro- and Nanofabrication Techniques To Create Superhydroph...mentioning
confidence: 99%
“…Several techniques have been developed or adapted to measure the adhesion, snap-in, pull-off, and friction forces of liquid drops on surfaces such as the use of tribometers [ 198 , 199 , 200 ], the surface forces apparatus (SFA) [ 201 , 202 ], atomic force microscopy [ 148 , 203 ], the centrifugal adhesion balance (CAB) [ 204 , 205 , 206 ], and microbalances including micro-electromechanical, micro-electrochemical, and microelectronics [ 107 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 ]. A Taylor–Couette cell has also been used to measure drag [ 216 ].…”
Section: Characterization Of the Static And Dynamic Wetting Propertie...mentioning
confidence: 99%
“…The hierarchical surface structure can be generated during the membrane fabricating process (using template substrate, 21 electrospinning 22 ) or post-modification of the synthesized membrane (plasma treatment, 23 layer-by-layer deposition using spraying/coating of nanoparticles 24 ). For example, Tan et al 25 prepared a superhydrophobic membrane with nano-and micro-roughness by dip-coating silicon dioxide (SiO 2 ) on the membrane surface.…”
Section: Introductionmentioning
confidence: 99%